Activation and tolerance of Siegesbeckia Orientalis L. rhizosphere to Cd stress - Xie, Jianyu; Xu, Xiaoxun; Zhang, Shirong; Yang, Zhanbiao; Wang, Guiyin; Li, Ting; Pu, Yulin; Zhou, Wei; Xu, Changlian; Lv, Guochun; Cheng, Zhang; Xian, Junren; et al. (Frontiers in Plant Science, 2023)
Investigating the rhizosphere microenvironment of hyperaccumulation under Cd stress will help to reveal the mechanism of Cd hyperaccumulate and tolerance. Thus, Cd fractions, the changes in chemical composition, and biochemical characteristics in rhizosphere soil of S. orientalis in response to Cd was investigated through a root bag experiment in this study. Cd induced the acidification of S. orientalis rhizosphere soil, and promoted the accumulation of dissolved organic carbon (DOC) and readily oxidizable organic carbon (ROC), which increased by 28.39% and 6.98% at the maximum compared with control. These were the key factors increase Cd bioavailability. In addition, rhizosphere microenvironment can alleviate the inhibition of Cd on soil biochemical properties. Under a certain concentration of Cd, the rhizosphere soil microbial biomass carbon (MBC), basal respiration, ammonification and nitrification were significantly increased (P < 0.05), and the activities of key enzymes were not significantly inhibited. Microorganisms and enzymes in rhizosphere soils can enhance S. orientalis tolerance to Cd, alleviating the nutrient imbalance and toxicity caused by Cd pollution. This study revealed the changes of physicochemical and biochemical properties of rhizosphere soil under Cd stress. Rhizosphere soil acidification and organic carbon accumulation are key factors promoting Cd activation, and microorganisms and enzymes are the responses of Cd tolerance.